Academic Motivation in Paramedical Students of Qom University of Medical Sciences: A Four-year Follow-up - fatemeh sharififard; hamid asayesh; abed asgari; Azam heidarpour; mahsa haji mohammad hoseini (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Motivation is an important factor in proper learning and education that affects various aspects of student behavior and performance in educational environments. Therefore, the present study aimed to determine the motivation of paramedical students at Qom University of Medical Sciences over a four-year period. Methods: This longitudinal survey study was conducted from 2017 to 2020, using a census method, on 76 (out of 81) students of anesthesia, operating room, and emergency medicine at the end of the first, third, fifth, and eighth semesters. The Vallerand Academic Motivation Scale with 28 items and 3 dimensions was completed by the participants. The responses to this scale are rated on a 7-point Likert, with a total score range of 28-196. Given the non-normal distribution of the data on the variable of academic motivation, the median and interquartile range were used to describe the data. The Friedman test was performed to compare academic motivation scores in different years of study. Values less than 0.05 were considered significant. Results: The median and interquartile range (IQR) of the academic motivation scores of the students participating in this study were 157.5 ± 23.5 in semester one, 146.1 ± 18.2 in semester three, 147 ± 17.8 in semester five, and 138.4 ± 5.3 in semester eight. The results of the Friedman test showed that there was a statistically significant difference between the total academic motivation scores of the students and their subscale scores in the four academic years; as a result, student motivation scores decreased as the academic year progressed. Conclusion: Based on the findings of this study, the total academic motivation score and the intrinsic and extrinsic subscales of students at the end of the fourth year of study had a significant decrease compared to the first year. Given that paramedics are in contact with patients and vulnerable people, they must be highly motivated during the stage of choosing a major, during their studies, after graduation, and during their employment in order to be able to provide appropriate services. Therefore, policymakers and academic professors should focus all their efforts on maintaining and increasing the motivation of paramedic students.